Status of terrestrial mammals in the Yangambi Landscape, Democratic Republic of the Congo - Vliet, N. van; Quintero, S.; Muhindo, J.; Nyumu, J.; Cerutti, P.O.; Nasi, R.; Rovero, F. (Cambridge University Press, 2023)
In this study we provide the first comprehensive camera-trap assessment of terrestrial mammals in the Yangambi landscape, comprising the Yangambi Biosphere Reserve and a logging concession in the Democratic Republic of the Congo. The terrestrial mammal community in this area exhibits lower occupancy and species richness compared to other conservation areas in the Congo Basin. The community is dominated by four species: Emin's pouched rat Cricetomys emini (1.3 kg), African brush-tailed porcupine Atherurus africanus (2.8 kg), blue duiker Philantomba monticola (5 kg) and bay duiker Cephalophus dorsalis (12 kg), which are known to be highly resilient. Large ungulates and medium-sized carnivores have particularly low abundances. Our study also confirmed the presence of four species categorized as threatened on the IUCN Red List: the chimpanzee Pan troglodytes, giant ground pangolin Smutsia gigantea, black-bellied pangolin Phataginus tetradactyla and white-bellied pangolin Phataginus tricuspis. Our findings highlight the need to consider wildlife conservation at the landscape level, including the logging concession, where species showed higher occupancy levels compared to the Biosphere Reserve, and highlighting the need for planning infrastructure construction and developing mitigation schemes, reducing forest degradation from logging and developing permanent cash crop agriculture. Landscape-level conservation will only be possible if a collaborative management model steered by local communities is developed with the participation of all constituencies.